Sistem Presentasi Cerdas Menggunakan Pengenalan Gerakan Tangan Berdasarkan Klasifikasi Dari Sinyal Electromyography (EMG) Menggunakan Myo Armband - Kusuma, Dedy Hidayat; Shodiq, Mohammad Nur (Universitas Nusantara PGRI Kediri, 2018)
Technological developments to support the current learning system are so fast that there is an interactive innovation technology for educational trends. One of the technologies implemented is an interactive presentation application in a multimedia class or smart presentation system. This technology makes it possible to control the presentation in a natural way with their hand movements. This introduction can replace conventional mouse roles and functions to facilitate teacher performance in applying interactive technology in the classroom. To build this intelligent presentation system, it is divided into several parts: 1) Recognition sensor arm movement using Myo armband; 2) Hand gesture of hand movements made several steps include: a) data retrieval based on realtime and wireless; b) feature extraction; c) classification using artificial neural network; and 3) Smart presentation, is a presentation system that can understand human behavior and provide interactive presentations.The expected benefits of the results of this study are, with the construction of intelligent presentation systems using hand-gesturing recognition based on the classification of electromyography signals, 1) Make presentations more efficient, engaging and easier to understand, and also make the discussion more interactive and improve communication; 2) Assists the presenter of material in exposing the material by using a presentation control system based on hand gestures.